Assessment of Semen Respiratory Activity of Domesticated Species before and after Cryopreservation: Boars, Bulls, Stallions, Reindeers and Roosters - Elena Nikitkina; Ismail Shapiev; Artem Musidray; Anna Krutikova; Kirill Plemyashov; Sofia Bogdanova; Victoria Leibova; Gennadiy Shiryaev; Julia Turlova (Veterinary Sciences, 2022)
To assess sperm quality, it is important to evaluate energy metabolism. The test substance 2.4-dinitrophenol (2.4-DNP) is an agent for destroying oxidative phosphorylation. 2.4-DNP shuts off the production of adenosine triphosphate (ATP) from oxidation and then, the respiration rate increases. If the respiratory chain is damaged, there is little or no response to adding 2.4-DNP. The aim of this study was to analyze the respiratory activity and oxidative phosphorylation in semen before and after freezing and compare the obtained data with the fertilizing ability of sperm. There was a reduction in sperm respiration rates in all species after thawing. The respiration of spermatozoa of boars, bulls, stallions, reindeers and chicken showed responses to 2.4-dinitrophenol. The only difference is in the strength of the response to the test substance. After freezing and thawing, respiratory stimulation by 2.4-DNP decreased. The results of our study show that respiration rate is not correlated with pregnancy rates and egg fertility. However, there was a high correlation between the stimulation of respiration by 2.4-dinitrophenol and pregnancy rates. The test for an increase in respiration rate after adding 2.4-dinitrophenol could be a suitable test of the fertilizing ability of sperm.